2020
DOI: 10.3892/or.2020.7878
|View full text |Cite
|
Sign up to set email alerts
|

Novel EGFR‑bispecific recombinant immunotoxin based on cucurmosin shows potent anti‑tumor efficiency in vitro

Abstract: Epidermal growth factor receptor (EGFR) is overexpressed in various tumors and is associated with cancer initiation, progression, and poor prognosis. Despite the achievements made by tyrosine kinase inhibitors and monoclonal antibodies in certain cases, many patients have not benefited from such treatment due to resistance. Immunotoxins (ITs) are antibody-cytotoxin chimeric molecules with specific cell killing ability, which have achieved different degrees of success in the treatment of a wide range of cancers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…Data of cell cycle analysis obtained from flow cytometry revealed that our recombinant IT arrests the HepG2 cell cycle at the G2 phase. Previous studies have been shown that ITs can impress cell cycles at G1/S phases [42][43][44]. Correlation among DNA fragmentation, apoptosis, and cell cycle arrest has been extensively investigated.…”
Section: Discussionmentioning
confidence: 99%
“…Data of cell cycle analysis obtained from flow cytometry revealed that our recombinant IT arrests the HepG2 cell cycle at the G2 phase. Previous studies have been shown that ITs can impress cell cycles at G1/S phases [42][43][44]. Correlation among DNA fragmentation, apoptosis, and cell cycle arrest has been extensively investigated.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, tumor growth was efficiently inhibited by one anti-HER2-PE24X7 immunotoxin in vivo ( Table 3 ) [ 59 ]. These studies demonstrate the potential of combining Nbs with toxins for the treatment of tumors [ 58 , 59 ].…”
Section: Antibodies Versus Nanobodies In Oncology Practicesmentioning
confidence: 98%
“…Moreover, an anti-EGFR Nb-cucurmosin immunotoxin was shown to inhibit the cell viability of EGFR-expressing tumor cell lines as well as induce HepG2 and A549 apoptosis (Table 3) [57]. More recently, Zhang et al (2020) demonstrated that a bispecific anti-EGFR-Nb-cucurmosin immunotoxin selectively kills cancer cells through apoptosis (Table 3) [58]. Cao et al (2020) produced three anti-HER-2 immunotoxins by linking anti-HER-2 sdAb to the PE24X7 toxin [59].…”
Section: Drug Deliverymentioning
confidence: 99%
See 1 more Smart Citation
“…Although “Bs” stands for bispecific, perhaps it would be more appropriate to use the denomination of biparatopic. In cytotoxicity assays with the CRC cell line SW1116, Bs/CUS had a 55-fold increase in activity at 72 h compared to rE/CUS [ 155 ]. Given the small size of each sdAb, the molecular weight of Bs/CUS (58 kDa) is still under the glomerular filtration threshold.…”
Section: Antibody Fragment-based Immunotoxins In Crc: Preclinical Developmentsmentioning
confidence: 99%